Analysis of a clinical case of primary hyperparathyroidism in combination with parathyroid adenoma and nodular goiter - S. N. Styazhkina; A. V. Ledneva; V. P. Byvaltseva; M. A. Michurina (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
The analysis of a clinical case of primary hyperparathyroidism in combination with parathyroid adenoma and nodular goiter is presented.